1991
DOI: 10.1142/s012908359100024x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Study of the Composition of Atmospheric Aerosols in Mexico City

Abstract: Elemental analysis of airborne particulates collected in a site near downtown Mexico City have been performed. The samples were taken during one week of every season in 1988, Twenty three elements, from sodium to lead, were detected by Proton Induced X-ray Emission (PIXE). In addition, soot contents was determined by laser Integrating Plate Method (LIPM). Concentrations of these elements show hourly variations during the day, with maximum values in the period from 6 to 12 A.M. An overall tendency toward maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…8 Using an independent station, for the period between 1993 and 1995, Castillejos et al 9 reported an average of 45 µg/m 3 for the southwestern part of Mexico City. This area has consistently been the low PM 10 concentration area, according to Cicero et al 5 and Edgerton et al 6 Characterizations of the chemical composition of the particulate also have been presented, including elemental ions [6][7][8]10 and organic carbon. 6,10 The studies pointed out a significant contribution of crustal material 8 specifically from the eastern end of the metropolitan area.…”
Section: Previous Studiesmentioning
confidence: 78%
See 1 more Smart Citation
“…8 Using an independent station, for the period between 1993 and 1995, Castillejos et al 9 reported an average of 45 µg/m 3 for the southwestern part of Mexico City. This area has consistently been the low PM 10 concentration area, according to Cicero et al 5 and Edgerton et al 6 Characterizations of the chemical composition of the particulate also have been presented, including elemental ions [6][7][8]10 and organic carbon. 6,10 The studies pointed out a significant contribution of crustal material 8 specifically from the eastern end of the metropolitan area.…”
Section: Previous Studiesmentioning
confidence: 78%
“…In independent studies, for the summer periods between July and August for the years 1987 to 1990, the average PM 15 concentration was reported at 133 µg/m 3 . 7 Subsequent studies on PM 15 reported average values of 106 µg/m 3 for the fall of 1993 at daytime in a southwestern site. 8 Using an independent station, for the period between 1993 and 1995, Castillejos et al 9 reported an average of 45 µg/m 3 for the southwestern part of Mexico City.…”
Section: Previous Studiesmentioning
confidence: 96%
“…), are environment due to the above activities is high, creating aerosols of nanoparticles. The composition of aerosols (respirable fraction < 2.5µm) over Mexico City has been studied in a series of recent articles (Aldape, et al, 1991a;Aldalpe, et al, 1991b;Aldalpe, et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Samples reported in this study were collected using high volume samplers as previously described (Aldape, et al, 1991a;Aldalpe, et al, 1991b;Aldalpe, et al, 1993). Six samples were collected at six sites in Mexico City: Nezahualcoyotl (A), Portales (B), Taxqueña (C), Nezahualcoyotl II (D), Hangares (E), and Secretaria de Hacienda (F).…”
Section: Methodsmentioning
confidence: 99%
“…Secondary organics are superimposed and can constitute 10 to 30% of RSP (Pandis et al, 1993). The aerosol system in Mexico City has also been intensely scrutinized through measurements (Aldape et al, 1991a(Aldape et al, and 1991b(Aldape et al, , 1993Miranda et al 1992 and1994). The diurnal pattern indicated by RSP and visibility data is qualitatively similar.…”
Section: The Urban Atmospherementioning
confidence: 99%